2014
DOI: 10.1080/00380768.2014.937674
|View full text |Cite
|
Sign up to set email alerts
|

Zinc fractions in soil and uptake by wheat as affected by different preceding crops

Abstract: Zinc (Zn) deficiency is widespread in alkaline and calcareous soils. Limited information is available on the effect of preceding crops on the distribution of Zn in soil solid phase. This field study was conducted to investigate the changes in Zn chemical forms in soil solid phase as affected by four preceding crops [Sunflower (Heilianthus annuus L. cv. Allstar), Sorghum (Sorghum bicolor L. cv. Speed Feed), Clover (Trifolium pratense L.) and Safflower (Carthamus tinctorius L. cv. Koseh-e-Isfahan)] in a calcareo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…In addition, the increases in the Fe-MnOx-Zn in B200 treatments might be due to an increase in ligand adsorption. Ligand adsorption usually suggests a negative charge is being conveyed onto the oxide surfaces, thus increasing Zn adsorption by Fe and Mn oxides in calcareous soil (Norouzi et al 2014). Similar results were also reported by Zahedifar (2017) in calcareous soils treated with wheat straw biochar.…”
Section: Availability and Chemical Fraction Of Zn In Soilsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, the increases in the Fe-MnOx-Zn in B200 treatments might be due to an increase in ligand adsorption. Ligand adsorption usually suggests a negative charge is being conveyed onto the oxide surfaces, thus increasing Zn adsorption by Fe and Mn oxides in calcareous soil (Norouzi et al 2014). Similar results were also reported by Zahedifar (2017) in calcareous soils treated with wheat straw biochar.…”
Section: Availability and Chemical Fraction Of Zn In Soilsupporting
confidence: 80%
“…Moreover, processing crop residues to biochar and applying it to calcareous soil are recognized as a better way for disposal of crop residue and improvement of soil quality (e.g., Beheshti et al 2018;Khadem and Raiesi). Hence, application of soil organic amendments such as biochar may help to increase soil organic matter and can subsequently increase availability and distribution of Zn fractions in calcareous soils (Khoshgoftarmanesh et al 2018;Norouzi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in accordance with the observation of Zhang et al [64], who reported that Zn application could increase Zn uptake by plants. Similar results were also reported in different crops by Harris et al [65], Norouzi et al [66], and Kumari et al [67].…”
Section: Zn Concentration and Uptakesupporting
confidence: 89%
“…Zn is often relatively low (< 0.5 mg kg -1 ), developing high-Zn-distribution cultivars should be 213 combined with agronomic measures like Zn fertilization to promote Zn uptake. For instance, in Iran 214 rainfed drylands with soil available Zn of 0.2 mg kg -1 (Norouzi et al, 2014), the tested wheat 215 cultivars exhibited high yield of 6.6 t ha -1 and shoot Zn uptake of 174 g ha -1 . Even if the Zn.c of 17.0 216 mg kg -1 was increased to the Zn.a of 26.4 mg kg -1 by introducing new cultivars, there was still a large 217 gap to Zn.t which needed to be closed by increasing Zn uptake.…”
Section: Quantify the Requirements To Achieve Wheat Zn Biofortificatimentioning
confidence: 99%